Evaluating the impact of testosterone replacement therapy on carotid atherosclerosis: a systematic review and meta-analysis - Syed Hamza Haider; Areeka Irfan; Samir Mustafa Sheikh; Muhammad Taha Abid; Turba Naz; Mudassir Abbas; Alishba Raza (Future Science OA)
Aim: This meta-analysis investigates the association between testosterone replacement therapy [TRT] and carotid artery atherosclerosis. Methods: 3 databases were searched for studies up to June 2023 per the PRISMA guidelines. The eligibility criteria comprised RCTs and observational studies involving hypogonadal males receiving exogenous testosterone, in which CIMT was assessed. CAA was the primary outcome, whereas secondary outcomes included HDL, LDL, CRP, total cholesterol and total testosterone. The statistical analysis was performed using Review Manager. Results: Statistical analysis revealed no association between TRT and assessed outcomes. There was a significant increase in total testosterone levels, depicting indirect anti-atherosclerotic effects of TRT. Conclusion: Meta-analysis shows no relation between TRT and CIMT or other markers, allowing its safe usage for hypogonadal males.